2013
DOI: 10.1177/230949901302100230
|View full text |Cite
|
Sign up to set email alerts
|

Legg-Calve-Perthes Disease in Two Generations of Male Family Members: A Case Report

Abstract: Legg-Calve-Perthes disease (LCPD) is a type of avascular necrosis of the femoral head occurring mainly in male children and causing early osteoarthritis. We report 2 generations of 4 male family members with LCPD-like features and mutation of the COL2A1 gene of the 12q13 chromosome. If LCPD occurs in any family member, we recommend genetic analysis and counselling as well as early radiological screening of related children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…COL2A1 mutations were also found in patients with a familial form of Legg‐Calve‐Perthes (MIM150600) disease and avascular necrosis of a femoral head (MIM 608805), (Al‐Omran & Sadat‐Ali, ; Andersen, Schantz, Bollerslev, & Justesen, ; Griffiths & Witherow, ; Li et al, ). Liu et al () reported three families with avascular necrosis of a femoral head caused by (p.Gly717Ser) and (p.Gly1170Ser) substitutions.…”
Section: Discussionmentioning
confidence: 99%
“…COL2A1 mutations were also found in patients with a familial form of Legg‐Calve‐Perthes (MIM150600) disease and avascular necrosis of a femoral head (MIM 608805), (Al‐Omran & Sadat‐Ali, ; Andersen, Schantz, Bollerslev, & Justesen, ; Griffiths & Witherow, ; Li et al, ). Liu et al () reported three families with avascular necrosis of a femoral head caused by (p.Gly717Ser) and (p.Gly1170Ser) substitutions.…”
Section: Discussionmentioning
confidence: 99%
“…Over 200 mutations have been identified in the COL2A1 gene, and the majority of these mutations have been associated with the replacement of Gly residues in the triple helix domain ( 13 ). In recent decades, an increasing number of studies have indicated that mutations in the COL2A1 gene are associated with familial or inherited ANFH ( 8 , 14 20 ). However, at present, no mutation hotspot has been confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of LCPD is unknown but is thought to result from vascular congestion and/or coagulation abnormalities in the circulation of the proximal femur [ 2 , 3 ]. The diagnosis has been associated with behavioral disorders [ 4 ], cigarette smoking [ 5 ], femoral and acetabular morphology [ 6 ], genitourinary anomalies [ 7 ], genetics [ 8 ], geography [ 1 ], childhood deprivation [ 9 , 10 ], and high-impact activities such as gymnastics [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%